2020
DOI: 10.1111/odi.13458
|View full text |Cite
|
Sign up to set email alerts
|

SNHG12/miR‐326/E2F1 feedback loop facilitates the progression of oral squamous cell carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is a prevalent cancer affecting the head and neck region (Bozec, Peyrade, Fischel, & Milano, 2009). It alarmingly represents approximately 3% of all malignant cases (Jin et al., 2016). OSCC is characterized by high morbidity and mortality, with more than 300,000 new OSCC cases and over 140,000 deaths of OSCC patients every year (Chi, Day, & Neville, 2015; Sasahira & Kirita, 2018). Although surgery combined with radiotherapy, neoadjuvant chemotherapy, and targeted therapy has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…In ICC, several lncRNAs such as lncRNA MT1JP and lncRNA AGAP2-AS1 have been shown to exhibit their tumor-related effects via sponging miRNAs to modulate the expression of various genes involved in tumor progression ( 25 , 26 ). Previously, SNHG12 was also reported to act as a ceRNA in several tumors, such as cervical cancer and oral squamous cell carcinoma ( 19 , 27 ). These findings encouraged us to explore the ceRNA mechanisms about SNHG12.…”
Section: Discussionmentioning
confidence: 99%
“…In ICC, several lncRNAs such as lncRNA MT1JP and lncRNA AGAP2-AS1 have been shown to exhibit their tumor-related effects via sponging miRNAs to modulate the expression of various genes involved in tumor progression ( 25 , 26 ). Previously, SNHG12 was also reported to act as a ceRNA in several tumors, such as cervical cancer and oral squamous cell carcinoma ( 19 , 27 ). These findings encouraged us to explore the ceRNA mechanisms about SNHG12.…”
Section: Discussionmentioning
confidence: 99%
“…56 Among several abnormally expressed lncRNAs, SNHG12 is often detected as an overexpressed lncRNA in this tumor and it was reported to regulate cell proliferation, migration, invasion, and EMT process via miR-326. 57 SNHG16 is another lncRNA closely associated with oral squamous carcinoma and its expression is correlated with c-Myc. It was reported to induce PCNA, MMP-2, MMP-9, E-cadherin along with reduction of N-cadherin and Snail starting the EMT induction.…”
Section: Head and Neck Cancersmentioning
confidence: 99%
“…A relatively uncommon malignant tumor affecting the head and neck regions is the oral squamous cell carcinoma characterized by a poor overall 5‐year survival rate 56 . Among several abnormally expressed lncRNAs, SNHG12 is often detected as an overexpressed lncRNA in this tumor and it was reported to regulate cell proliferation, migration, invasion, and EMT process via miR‐326 57 . SNHG16 is another lncRNA closely associated with oral squamous carcinoma and its expression is correlated with c‐Myc.…”
Section: Small Nucleolar Rna Host Genes In Emt Processmentioning
confidence: 99%
“…Accumulating studies have indicated the influence of long noncoding RNAs (lncRNAs) on the progression of many diseases [ 8 ]. LncRNAs are non-coding RNAs with a length larger than 200 nucleotides.…”
Section: Introductionmentioning
confidence: 99%